Primary gastric choriocarcinoma: A case report - Barreda Bolaños, Fernando (2019)
Primary gastric choriocarcinoma (PGC) is an uncommon tumor. Due to its rarity, its pathogenesis is still unclear. The diagnosis is based on immunohistopathology, which is positive for human chorionic gonadotropin (hCG). It is a highly invasive and rapidly-disseminated hematogenous neoplasm, which leads to a poor prognosis. We present the case of a 57-year-old woman with upper gastrointestinal bleeding associated with weight loss. The gastroscopy showed, on the cardia and paracardial region, a 5x4-cm ulcerated polypoid lesion with circumscribed edges and without adjacent wall infiltration, with stigmas of recent bleeding and a pathological anatomy that demonstrates ulcerated pleomorphic malignancy with positive immunohistochemistry for pankeratin. Given the suspicion of poorly differentiated carcinoma and without evidence of metastasis, the patient underwent a total gastrectomy and the pathology was compatible with choriocarcinoma. Therefore, after the surgery, a serum hCG test was performed with a result of 714 mIU/ml, which further confirmed the diagnosis. Treatment with adjuvant chemotherapy was decided, and a tomographic and serological hCG follow-up was conducted, without the presence of active disease.